A Study of Employee Satisfaction in the Banking Sector of Chandigarh: Exploring the Relationship between Job Satisfaction and Work Performance in the Banking Sector of Chandigarh (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Because banks are the backbone of any country, their contribution to the country should bemaximised. In related disciplines such as industrial-organizational psychology, organisationalbehaviour, personnel and human resource management, and organisational management, jobsatisfaction is one of the most generally discussed and enthusiastically investigated phenomena. Jobsatisfaction refers to the employee's positive or negative attitude toward his or her work, as well as thedegree of agreement between one's expectations of the employment and the benefits that the job offers.These attitudes are related to the job in terms of salaries, employment supervisors, working conditions,social relationships on the job, timely resolution of grievances, and fair treatment by the employer.In India, the banking sector has long been one of the most popular places to work. The banking sectorhas emerged as a sunrise sector in the Indian economy in this decade. 'A satisfied employee is aproductive employee,' as the saying goes. This research will look into how much job satisfactioncontributes to strong work performance and what factors influence employee job satisfaction